Premature and accelerated aging: HIV or HAART? - Smith, Reuben L.; de Boer, Richard; Brul, Stanley; Budovskaya, Yelena V.; van der Spek, Hans (Frontiers in Genetics, 2013)
Highly Active Anti-Retroviral Therapy (HAART) has significantly increased life expectancy of the HIV-positive population. Nevertheless, the average lifespan of HIV patients remains shorter compared to uninfected individuals. Immunosenescence, a current explanation for this difference invokes heavily on viral stimulus despite HAART efficiency in viral suppression. We propose here that the premature and accelerated ageing of HIV patients can also be caused by adverse effects of antiretroviral drugs, specifically those that affect the mitochondria. The Nucleoside Reverse Transcriptase Inhibitor (NRTI) antiretroviral drug class for instance, is known to cause depletion of mitochondrial DNA via inhibition of the mitochondrial specific DNA polymerase-ƴ. Besides NRTIs, other antiretroviral drug classes such as Protease Inhibitors also cause severe mitochondrial damage by increasing oxidative stress and diminishing mitochondrial function. We also discuss important areas for future research and argue in favour of the use of C. elegans as a novel model system for studying these effects.